2020
DOI: 10.1186/s12883-020-02020-8
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing factors and radiological features in patients with internal carotid artery dissection or vertebral artery dissection

Abstract: Background Cervicocerebral artery dissection is an important cause of ischemic stroke in young and middle-aged individuals. However, very few studies have compared the differential features between internal carotid artery dissection (ICAD) and vertebral artery dissection (VAD), including both cervical and intracranial artery dissections. We conducted a study to investigate the predisposing factors and radiological features in patients with ICAD or VAD. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Compared with the cervical artery, the intracranial artery relatively lacks elastic fibers in the media and adventitial tissue and has no external elastic layer [ 8 , 33 ]. Therefore, intracranial dissection is more likely to develop dissecting aneurysms due to the lack of supporting tissue in the vessel [ 34 ]. The reason why aneurysms are more commonly found in the posterior circulation in the intradural dissection is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the cervical artery, the intracranial artery relatively lacks elastic fibers in the media and adventitial tissue and has no external elastic layer [ 8 , 33 ]. Therefore, intracranial dissection is more likely to develop dissecting aneurysms due to the lack of supporting tissue in the vessel [ 34 ]. The reason why aneurysms are more commonly found in the posterior circulation in the intradural dissection is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…8,33 Therefore, intracranial dissection is more likely to develop dissecting aneurysms due to the lack of supporting tissue in the vessel. 34 The reason why aneurysms are more commonly found in the posterior circulation in the intradural dissection is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the risk of recurrent cerebral infarction or arterial dissection is low after 3-6 months [27,28]. Antiplatelet and anticoagulant therapies are therefore particularly recommended to prevent recurrence only during the period from 3 to 6 months after onset [27,29]. If possible, imaging investigations should be conducted every 3 months, and the necessity of antiplatelet or anticoagulant therapy and the choice of drug should be considered based on the resulting ndings.…”
Section: Treatment Of Unruptured Vertebral Basilar Artery Dissectionmentioning
confidence: 99%
“…In the event of arterial dissection, however, the inner surface of the vascular lumen becomes smooth as a result of the repaired intima, and with this structure, thrombi are unlikely to form. It has also been shown that the risk of recurrent cerebral infarction or arterial dissection is low after 3-6 months [27,28]. Antiplatelet and anticoagulant therapies are therefore particularly recommended to prevent recurrence only during the period from 3 to 6 months after onset [27,29].…”
Section: Treatment Of Unruptured Vertebral Basilar Artery Dissectionmentioning
confidence: 99%
See 1 more Smart Citation